Pelanggaran Etika Pariwara Indonesia pada Iklan Pembesar Kelamin Prostanore di Platform Digital - Sheilla Ekawati; Farrel Aditya; Muhammad Fawwaz Fauzarrahman; Fajar Junaedi (Universitas Muhammadiyah Klaten, 2025)
This study aims to analyze the violations of the Indonesian Advertising Ethics in the advertisement of the Prostanore male enhancement product, which has raised concerns due to its potential impact on society. Utilizing a descriptive qualitative method and a postpositivist paradigm, this research collected data through documentation and literature review, and analyzed the advertisement found on digital platforms. The findings indicate that the Prostanore advertisement violates several provisions of the Indonesian Advertising Ethics, including airing on media not suitable for an adult demographic and making exaggerated claims about the product's efficacy. Additionally, the use of misleading terms such as